2015
DOI: 10.1007/s11164-015-2150-y
|View full text |Cite
|
Sign up to set email alerts
|

Poly(vinylpyrrolidinium) perchlorate as a new and efficient catalyst for the promotion of the synthesis of polyhydroquinoline derivatives via Hantzsch condensation

Abstract: A green approach for the promotion of the synthesis of Hantzsch products using poly(vinylpyrrolidinium) perchlorate {[PVPH]ClO 4 } as a new modified polymeric catalyst in the absence of solvent is reported. The title catalyst is easily prepared and characterized using a variety of techniques including infrared spectra, X-ray diffraction, thermal gravimetric analysis, scanning electron microscopy, pH analysis, and Hammett acidity function. Some of the advantages of this novel synthetic method are: easy preparat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 39 publications
(41 reference statements)
0
6
0
Order By: Relevance
“…In continuation of our previous studies on the introduction of new catalysts for the promotion of multi‐component reactions [44–48] and specially bio‐organic ones, [49–51] in this investigation concurrent generation of carboxylic acids from the aerobic oxidation of aldehydes leading to α ‐acyloxycarboxamides with an stereogenic center and considerable ee by the supporting role of Pregabalin as an efficient reagent under the auxiliary of water is reported. It should be noted that although the role of amino acids in reaction with isocyanide and aldehydes was studied in the Ugi's reaction, [52–53] in this work we showed that by changing of the solvent and temperature the same reaction can lead to the production of the asymmetric Passerini's products (Scheme 3).…”
Section: Introductionmentioning
confidence: 70%
“…In continuation of our previous studies on the introduction of new catalysts for the promotion of multi‐component reactions [44–48] and specially bio‐organic ones, [49–51] in this investigation concurrent generation of carboxylic acids from the aerobic oxidation of aldehydes leading to α ‐acyloxycarboxamides with an stereogenic center and considerable ee by the supporting role of Pregabalin as an efficient reagent under the auxiliary of water is reported. It should be noted that although the role of amino acids in reaction with isocyanide and aldehydes was studied in the Ugi's reaction, [52–53] in this work we showed that by changing of the solvent and temperature the same reaction can lead to the production of the asymmetric Passerini's products (Scheme 3).…”
Section: Introductionmentioning
confidence: 70%
“…4c) was achieved efficiently from the benzaldehyde derivatives (1 mmol), dimedone (1 mmol) and ethyl acetoacetate (1 mmol) in the presence of NSCH at 80°C under solvent-free condition. The results are listed in Table 2 (entries [18][19][20][21][22]. Two alternative reaction pathways to achieve this outcome are shown in Fig.…”
Section: Evaluation Of the Catalytic Activitymentioning
confidence: 97%
“…[12][13][14] Xanthene, chromene and hydroquinoline derivatives are important organic compounds with a wide range of applicability and biological activity. [15][16][17][18][19][20] Although some synthetic methodologies have been reported for each class of these compounds in the literature, [21][22][23][24][25][26][27][28][29][30][31][32] each with their own advantages, many of them suffer from some disadvantages. The use of homogeneous acid catalysts may result in some difficulties with product separation and purification, low yield, long reaction time, use of toxic organic solvents and harsh reaction procedures.…”
Section: Introductionmentioning
confidence: 99%
“…Mosaddegh's group succeeded in synthesizing phthalazinetriones derivatives through a rapid, one-pot, four-component route by using Ce(SO 4 ) 2 4H 2 O at 125 • C and under solvent-free conditions [23]. However, some methods experienced some limitations such as tedious workup procedures, using corrosive catalysts, low product yields, long reaction times, formation of side products, and difficulties in recovery of catalysts [24].…”
Section: Introductionmentioning
confidence: 99%